The effect of antibiotic prescription in non-critically ill hospitalized patients with COVID-19: A Japanese inpatient database study. - Haruka Imai; Jun Suzuki; Tomoki Mizuno; Shota Takahashi; Hideya Itagaki; Makiko Yoshida; Shiro Endo; Eiichi N Kodama (PLoS ONE)
Background Coronavirus disease 2019 (COVID-19) is an ongoing global pandemic. Bacterial coinfections with COVID-19 occur in 3.5% of COVID-19 cases, with a higher incidence in severe cases. Although antibiotics have been prescribed to treat non-critically ill patients with COVID-19, their effect on non-critically ill hospitalized patients with COVID-19 remains uncertain. Methods We analyzed data from non-critically ill hospitalized patients with COVID-19 who were older than 18 years between January 1, 2020, and May 31, 2023. We performed propensity score matching analysis, evaluating in-hospital mortality with or without antibiotic prescription within 2 days of admission. Sensitivity analyses using inverse probability weighting and generalized estimating equation were also performed. Results Eligible patients (n =  144,110) were divided into antibiotic prescription (n =  3,873) and control (n =  140,237) groups. One-to-one propensity score matching identified 3,861 pairs of patients who received antibiotic prescriptions within 2 days of admission. Following this, antibiotic prescription was associated with a decreased 28-day mortality rate (2.3% vs. 3.6%) and in-hospital mortality rate (4.0% vs. 5.0%) compared with the control group. Conversely, antibiotics increased Clostridioides difficile infection (CDI) compared with the control group (0.6% vs. 0.1%). No statistical differences were observed between both groups regarding acute kidney injury (0.4% vs. 0.2%). Sensitivity analysis showed similar outcomes. Conclusions This multicenter observational study in Japan showed that antibiotic prescriptions were associated with lower 28-day and in-hospital mortalities and an increased CDI risk in non-critically ill hospitalized patients with COVID-19.